2022
DOI: 10.1111/etho.12348
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Culture: A Framework

Abstract: Cognitive culture theory and the associated methods of cultural domain analysis and cultural consensus analysis have revolutionized the study of cultural sharing and variation. However, the ways in which these methods can be employed are still not widely appreciated. Our aim in this paper is to propose a systematic framework for investigating cultural models. We provide examples of ideal types of sharing and variation in cultural models, including monocentric cultural models, multifocal cultural models, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, the cultural model of family life in Brazil is overwhelmingly shared; however, in terms of the features contributing to a "good" Brazilian family, there is a systematic tendency for lower class respondents to emphasize rules, organization, and the patrifocal authority structure as most important, while middle-class respondents emphasize love, mutual understanding, and an emotional sense of union (Dressler et al, 2015). Everyone agrees that family organization and family emotional climate are important, but some respondents privilege one set of features over another (Henderson et al, 2022, for an extended discussion). Finally, the approach can be used in the study of culture change even with cross-sectional designs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cultural model of family life in Brazil is overwhelmingly shared; however, in terms of the features contributing to a "good" Brazilian family, there is a systematic tendency for lower class respondents to emphasize rules, organization, and the patrifocal authority structure as most important, while middle-class respondents emphasize love, mutual understanding, and an emotional sense of union (Dressler et al, 2015). Everyone agrees that family organization and family emotional climate are important, but some respondents privilege one set of features over another (Henderson et al, 2022, for an extended discussion). Finally, the approach can be used in the study of culture change even with cross-sectional designs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Henderson et al. (in press) have demonstrated that there is at least one other possibility: that there are multiple cultures in the sample. They describe the configuration of data presented in Figure 1 as “multicentric,” referring to two non‐connecting centres of knowledge on a single dimension of a cultural model.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a single culture, residual agreement analysis describes intracultural variation. If the “single culture” assumption is violated (i.e., the ratio of the first and second eigenvalues is less than 3:1), residual agreement analysis determines whether there is no cultural model (i.e., people responded in largely idiosyncratic, rather than patterned, ways), or whether there are multiple cultural models (Henderson et al., in press). For understanding the cause of intracultural variation, residual agreement coefficients are regressed on hypothesized variables of interest.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, there has been a greater appreciation for how disagreement and alternative experiences are patterned within a defined population 21,22 . In other words, there are shared experiences (e.g., patient recurrence after treatment) that involve shared considerations (e.g., factors that impact psychological/emotional response) that may be idiosyncratically employed by individuals.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, there has been a greater appreciation for how disagreement and alternative experiences are patterned within a defined population. 21 , 22 In other words, there are shared experiences (e.g., patient recurrence after treatment) that involve shared considerations (e.g., factors that impact psychological/emotional response) that may be idiosyncratically employed by individuals. In this case, we sought to determine whether individuals who experienced greater emotional or psychological responses after patient recurrence on an optimization trial discussed decisional factors in the same manner as those who did not perceive a difference between optimization and traditional trials.…”
Section: Methodsmentioning
confidence: 99%